Methods for quantifying the stable sintering region in laser sintered polyamide-12 - Mike Vasquez; Barry Haworth; Neil Hopkinson (2013)
Manufacturing complex parts by the laser sintering process requires a minimum amount of energy input for consolidation of polymer particles to occur; however too much energy can result in a decline in mechanical properties. This decrease is thought to be the result of polymer chain degradation. A stable sintering region (SSR) has been proposed to describe the optimum temperature range for successful laser sintering. This article will aim to quantify the SSR for polyamide-12 by using thermogravimetric analysis (TGA) to provide a framework for identifying key laser sintering processing parameters. Weight loss with respect to temperature is the main measurement output of the TGA procedure. However, the precise temperature and thermal history of a material is difficult to quantify during the laser sintering process; instead an energy input approach has been developed. A degradation energy was calculated from the TGA data and was used in conjunction with a laser sintering formula called energy melt ratio to prescribe build parameters for laser sintered parts. The mechanical properties of these parts illustrated the effect of degradation at various levels of energy input. Implications for this work include optimizing the material selection process for polymer laser sintering materials beyond polyamide-12. © 2012 Society of Plastics Engineers.